The role of marriage in the causal pathway from economic conditions early in life to mortality - Gerard J. van den Berg; Sumedha Gupta (Institute for Labour Market Policy Evaluation (IFAU), 2011)
This paper analyzes the interplay between early-life conditions and marital status, as determinants of adult mortality. We use individual data from Dutch registers (years 1815-2000), combined with business cycle conditions in childhood as indicators of earlylife conditions. The empirical analysis estimates bivariate duration models of marriage and mortality, allowing for unobserved heterogeneity and causal effects. Results show that conditions around birth and school ages are important for marriage and mortality. Men typically enjoy a protective effect of marriage on mortality, whereas women suffer during childbearing ages. Having been born under favorable economic conditions reduces female mortality during childbearing ages.
Keywords: I12; J14; E32; N33; N13; C41; 330; death; longevity; recession; life expectancy; lifetimes; marital status; timing of events; selectivity; health; Sterblichkeit; Ehe; Lebensstandard; Geschlecht; Sozialgeschichte; Niederlande